Turkish folk medicinal plants, part III: Sile (Istanbul) - (:unkn) unknown (ELSEVIER SCIENCE BV, 2000)
In this paper, forty-three folk medicinal plants from Sile (Turkey) have been reported. Among them 35 species were wild and eight species were cultivated plants. The folk medicinal plants have been mostly used for the treatment of eczema, stomach and kidney ailments, asthma, cough, diabetes, and wounds. (C) 2000 Elsevier Science B.V. All rights reserved.
Keywords: folk medicine; medicinal plants; Turkey